Potential for biogas production and utilisation based on regionally available substrates - Kamarád, L.; Digtiar, S.; Meixner, K. (Панорама, 2018)
The presentation will give an overview about regionally available materials and biodegradable residues (substrates), which are potentially suitable for biogas production. There will be discussed possibilities for mono-digestion and co-digestion of specific substrates (e.g. nitrogen-rich materials, algae etc.), considering theirs potential and eventual troubleshooting. Data from several national and international projects will give an information about potentials of the biogas technology. The best practice examples will show gained experiences made by already implemented projects.